Sublethal and lethal effects on Rhinella Arenarum (Anura, Bufonidae) tadpoles exerted by the pirimicarb-containing technical formulation insecticide Aficida® - Vera Candioti, Josefina (2010)
Acute toxicity, genotoxicity, and cytotoxicity of the pirimicarb-containing commercial-formulation carbamate insecticide Aficida® (50% pirimicarb) were evaluated on Rhinella arenarum (Anura, Bufonidae) tadpoles exposed under laboratory conditions. Lethal and sublethal effects were employed as bioassays for acute toxicity, whereas micronuclei (MNi) induction and alterations in the ratio erythrocytes:erythroblasts were employed as end-points for genotoxicity and cytotoxicity, respectively. Cr(VI) (23 mg L-1) and cyclophosphamide (40 mg L-1) were employed as positive controls for toxicity and geno-cytotoxicity assays, respectively. In Gosner stage 25 (STD25), the results revealed mean values of 402.0 and 223.6 mg Aficida® L-1 for LC-5024 h and LC-5096 h, respectively. When STD37-39 tadpoles were exposed, the LC-5024 h and LC-5096 h reached values of 239.4 and 181.7 mg Aficida® L-1, respectively. Sublethal effects revealed a mean EC-5096 h of 133.85 and 104.2 mg Aficida® in those STD25 and STD37-39 treated tadpoles, respectively. The results demonstrated that in 48-h-exposed tadpoles, a MNi increase was found only in those 80.0 mg L-1 Aficida®-treated individuals. When tadpoles were exposed to Aficida® for 96 h, only the 160 mg L-1-treated individuals showed a significant increase in MNi frequency. Concentrations ranging from 80.0 to 250.0 mg Aficida® L-1 resulted in cellular cytotoxicity, revealed by a decreased proportion of circulating erythrocytes and an enhancement of erythroblasts. Accordingly, this species could provide a suitable and useful experimental model for biomonitoring aquatic ecosystems. © 2009 Elsevier Ltd. All rights reserved.